Kepadatan dan Pola Distribusi Teripang Hitam (Holothuria atra) di Pesisir Pantai Haenesai Desa Hulung, Kabupaten Seram Bagian Barat - Iloni Touwe; Handy Erwin Pier Leimena; Evelin Tuhumuri (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
The black sea cucumber (Holothuria atra) holds significant ecological and economic value in tropical marine ecosystems, including those of Maluku, Indonesia. This study aimed to estimate population density, spatial distribution patterns, and their relationship with environmental conditions along the Haenesai coast, Hulung Village, Taniwel District, West Seram Regency. Sampling was carried out using the belt transect method (50 m × 2 m) at three stations with three replications, while physicochemical parameters of seawater (temperature, salinity, pH, dissolved oxygen, and transparency) were measured in situ. A total of 96 individuals of H. atra were recorded, with an average density of 10.6 ind/100 m². Station I exhibited the highest density (13 ind/100 m²), whereas Station II showed the lowest (9.3 ind/100 m²). Distribution patterns were generally uniform at Stations I and II, while Station III displayed a clustered pattern. These variations are likely influenced by differences in water transparency, dissolved oxygen, and substrate heterogeneity that affect food availability. Overall, environmental conditions remained suitable for H. atra, although evidence of exploitation pressure from local harvesting was observed. Ecologically, H. atra plays a critical role as a bioturbator, maintaining sediment quality and coastal ecosystem stability. This study highlights the need for regulated harvesting, habitat protection, and aquaculture development as strategic measures for the sustainable management of sea cucumber resources in Maluku.